Acute pancreatitis associated with dengue fever: An interesting and rare complication of dengue virus - Mishra, Arvind; Saini, Rohin; Kallani, Monika (Indian Journal of Case Reports, 2019)
In humans, infections with dengue viruses range from mild fever with thrombocytopenia to life-threatening forms like vasodilatory shock with hemorrhagic manifestations. Of the many complications known of dengue fever, pancreatitis is a rarely discussed event. We would like to present a rare and unusual complication of this common disease. A 17 year old female with past history of tuberculosis was admitted with complains of pain abdomen and fever along with thrombocytopenia. Besides features of dengue fever, the presence of typical abdominal pain, high serum amylase, ultrasound, and computerized tomography scan features suggested the diagnosis of an acute pancreatitis. This complication developed in the initial phase of the illness. The patient had mild-to-moderate pancreatitis that recovered uneventfully with conservative treatment. The awareness of this complication in dengue fever is necessary for timely management of patients which will aid in reducing mortality.